2022
DOI: 10.5014/ajot.2022.048736
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Daily Activities Among Women 5 Years After Breast Cancer

Abstract: Importance: Understanding the long-term participation restrictions after breast cancer (BC) is crucial for developing occupation-based interventions. Objective: To (1) compare women’s participation during the BC subacute phase (2 yr postdiagnosis) with the chronic (5 yr postdiagnosis) phase, (2) explore factors associated with participation in the chronic phase, and (3) describe strategies women use to overcome participation restrictions. Design: Descriptive longitudinal study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Rachel's weakness and confidence affected her ability to dress and Elizabeth's ability to walk. These findings were expected since evidence reports that occupations requiring the most physical, emotional and cognitive skills are usually most impacted by cancer treatment side effects (Fangel et al, 2013;Loubani et al, 2022). While these cancer treatment effects are well documented in the literature, our study also presented the role of the environment, including social groups of support and technology, to facilitate occupational participation of cancer survivors and, therefore, a way to support their occupational identity (Nizzero et al, 2017).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Rachel's weakness and confidence affected her ability to dress and Elizabeth's ability to walk. These findings were expected since evidence reports that occupations requiring the most physical, emotional and cognitive skills are usually most impacted by cancer treatment side effects (Fangel et al, 2013;Loubani et al, 2022). While these cancer treatment effects are well documented in the literature, our study also presented the role of the environment, including social groups of support and technology, to facilitate occupational participation of cancer survivors and, therefore, a way to support their occupational identity (Nizzero et al, 2017).…”
Section: Discussionsupporting
confidence: 64%
“…Since the aim of the study was to explore the lived experience of participants, we did not focus in depth on details of variables such as breast cancer characteristics, cancer treatment and demographics of participants; instead, we wanted to know their experience regarding occupational identity, congruent with the studies of Palmadottir (2009) and McGrath (2013). Moreover, recent evidence did not identify correlations between those characteristics and participation in meaningful occupation in women after breast cancer in their chronic phase; 5 years after treatment (Loubani et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Occupational therapists approach the rehabilitation of breast cancer patients from a holistic perspective, considering not only physical symptoms but also cognitive, emotional, and social aspects that influence the recovery process (Désiron et al, 2015; Loubani et al, 2022; Lozano-Lozano et al, 2023). This approach takes into account roles, interests, habits, routines, performance contexts, competencies, physical and emotional abilities, as well as personal backgrounds («Occupational Therapy Practice Framework», 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cancer survivors often experience unmet occupational needs in areas such as personal care, instrumental activities, social participation, work, and education (Algeo et al, 2021; Brick et al, 2022; Loubani et al, 2022; Stevens et al, 2020). Thus, OT interventions for breast cancer survivors should primarily focus on enhancing occupational performance and improving HRQoL (Lai et al, 2021; Loubani et al, 2022). The main objective of this study was to examine the impact of breast cancer on occupational performance in order to develop an App aimed at improving functionality and occupational performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation